2021
DOI: 10.1021/acsomega.1c00992
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Delivery of MicroRNA-7 Targeting EGFR to Inhibit the Growth, Invasion, and Migration of Ovarian Cancer

Abstract: Ovarian cancer is highly aggressive and has high rates of recurrence and metastasis. Due to the limited effects of current treatments, it is necessary to conduct research and develop new treatment options. The application of gene therapy in tumor therapy is gradually increasing and has exciting prospects. MicroRNA-7 (miR-7) has been reported to inhibit the growth, invasion, and metastasis of a variety of solid tumors. Cationic liposomes are safe and effective gene delivery systems for transfection in vivo and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…Together our study unravels an interesting aspect that despite multiple predicted targets for miRNA, only a few targets are significantly altered which may contribute to the overall phenotype. However, this also suggests that the idea to use miRNA-7 as a potential anti-cancer therapeutic 26 may have to be carefully determined given the adverse remodeling observed with cardiomyocyte expression of miRNA-7, an observation reminiscent of anthracycline mediated cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Together our study unravels an interesting aspect that despite multiple predicted targets for miRNA, only a few targets are significantly altered which may contribute to the overall phenotype. However, this also suggests that the idea to use miRNA-7 as a potential anti-cancer therapeutic 26 may have to be carefully determined given the adverse remodeling observed with cardiomyocyte expression of miRNA-7, an observation reminiscent of anthracycline mediated cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, modified and unmodified LNPs have been used to deliver miRNA previously. Cationic liposomes have been used as transfection agents to deliver miRNA such as miR-7 to ovarian cancer cells, miR-143 and -145 in human colorectal tumors, and miR-122 in liver cells achieving up to 80% efficiency [86,124,125]. Cationic liposomes typically consist of a cationic lipid, neutral lipid and/or cholesterol, and a PEG-lipid.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA uptake's temporal efficiency depends on the miRNA endocytotic mechanism, the miRNA carrier vehicle, and the miRNA type [86,87]. For example, the miRNA uptake of a human ovarian cancer cell line treated with liposomes loaded with fluorescently-labeled hsa-miR-7-5p increased linearly over 24 hours [86]. The uptake of miRNA in multiple myeloma treated with stable nucleic acid-lipid particles (SNALPs) loaded with hsa-miR-34a decreased after 48 hours [87].…”
Section: The Dynamic Light Scattering (Dls) Technique Reveals How Different Processes Affect Vesicle Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al showed that miR-203-loaded liposomes silence slug expression in vitro and in vivo, inhibit the TGF-β1/Smad pathway in triple-negative breast cancer cells, and improve the anticancer effects of chemotherapy [91]. miR-7-loaded cationic liposomes inhibit epidermal growth factor receptor (EGFR) and suppress the spread of ovarian cancer [92]. Moreover, Zhang et al reported that transferrin-targeted miR-221 inhibitor-loaded liposomes show a 15-fold higher delivery to HepG2 cells than nontargeted liposomes and increase the expression levels of miR-221 targets, suggesting efficient delivery [93].…”
Section: Cell-based Delivery Systemsmentioning
confidence: 99%